From Centralized Exchanges to Decentralized Exchanges: Limitations of Regulation of the Minister of Finance Number 50 of 2025 and the Redesign of Protocol-Based Crypto Asset Taxation - Muchamad Irham Fathoni; Akbar Saputra (Unit Penerbitan Politeknik Keuangan Negara STAN, 2025)
This study analyzes the effectiveness and limitations of the Minister of Finance Regulation (PMK) Number 50 of 2025 in the taxation of crypto assets amid the shift from centralized exchanges to decentralized exchanges. Employing a qualitative approach with a policy study design, data were collected through a literature review of domestic regulations, international guidelines, and academic publications. The theoretical framework encompasses critical realism, deterrence theory, legal and institutional theory, and behavioral economics. The main findings indicate that PMK Number 50 of 2025 is administratively effective in centralized exchanges, as it relies on the designation of tax collectors, user identification through Know Your Customer (KYC) procedures, and a withholding-at-source mechanism. However, the regulation is incompatible with the characteristics of decentralized exchanges, which are permissionless, noncustodial, pseudonymous, and cross-jurisdictional. Consequently, this creates an illusion of compliance, tax gaps, and horizontal inequity between participants in centralized and decentralized exchanges. Policy implications include the need to shift from entity-based collection toward compliance by design at the protocol level, expanding tax capture at on-ramp and off-ramp gateways, utilizing on-chain analytics and blockchain forensics, and adopting cross-border information exchange standards such as the Crypto-Asset Reporting Framework and the Travel Rule. Concrete recommendations involve developing a regulatory sandbox for regulated decentralized finance, integrating tax-reporting oracles into smart contracts, and strengthening the institutional capacity of the Directorate General of Taxes through a center of excellence for digital taxation.